Four species of the genus Seba from Japan, with descriptions of two new species (Crustacea: Amphipoda: Sebidae) - Ariyama, Hiroyuki (Zootaxa, 2009)
Four species of the genus Seba Bate, 1862 were collected from coastal areas in western Japan. Among them, two species were revealed to be new to science. Species collected are Seba chiltoni Moore, 1987, S. ekepuu J.L. Barnard, 1970, S. latiquinta sp. nov., and S. latisexta sp. nov. All of them are described in both sexes, and keys to species of Seba in Japan are provided. Each species is distinguishable from one another by the shapes of gnathopods, pereopods 5–7 and uropods 1 and 2. The genus Caribseba Shaw, 1989 is synonymized with Seba.